2015
DOI: 10.15713/ins.jcri.36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microvessel density in central and peripheral giant cell granulomas

Abstract: Background: Angiogenesis in the physiological status, balance is maintained between the pro-and anti-angiogenic factors and it is required for a tumor to grow beyond 1-2 mm in diameter. In central giant cell granuloma (CGCG) and peripheral giant cell granuloma (PGCG) the origin of giant cells, clinicopathological features overlap, but still there is a difference in the biological behavior. We aimed to assess the possible role of angiogenesis and presence of macrophages by the expression of CD34 and CD68 respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
5
2
Order By: Relevance
“…Our results are in accordance with the results of previous studies as that of Hallikeri et al, 2015 andSouza et al, 2000 in which the expression of Ki-67 was mainly restricted to mononuclear cells while few giant cells showed positive reactivity. They suggested that mononuclear cells are the proliferative components of PGCG 10,49 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with the results of previous studies as that of Hallikeri et al, 2015 andSouza et al, 2000 in which the expression of Ki-67 was mainly restricted to mononuclear cells while few giant cells showed positive reactivity. They suggested that mononuclear cells are the proliferative components of PGCG 10,49 .…”
Section: Discussionsupporting
confidence: 93%
“…To provide appropriate treatment, the pathogenesis of the lesions is very important 10 . However, the origin of giant cell lesions of oral cavity has been subjected to controversy for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Mean vascular density is commonly used as a critical prognostic marker of neoplasms; therefore our findings indicate that central giant cell granuloma is more aggressive and invasive than AM, OKC and PG (Maeda et al, 1995). In the present study, mean vascular density for Central Giant Cell Lesion was 32.99±0.77, this is in line with the findings of , who used CD34 as a marker of angiogenesis (Hallikeri et al, 2015). Furthermore, macrophages are associated with the angiogenesis in tumor stroma, thereby stimulating and modulating angiogenic process.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, macrophages are associated with the angiogenesis in tumor stroma, thereby stimulating and modulating angiogenic process. This is supported by the high presence of macrophages in giant cell lesions with comparative ratios to blood vessels (Hallikeri et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…On the contrary to the findings of the present study, N Mohtasham et al (13) , Kumar et al (14) ,HJ Sherlin et al (15) and Hallikeri K et al (16) supposed a macrophage origin for MNGCs of CGCG and PGCG lesions .…”
Section: Ghaly Amcontrasting
confidence: 99%